Utilizing CaCO3, CaF2, SiO2, and TiO2 particles to enhance color homogeneity and luminous flux of WLEDs - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
The chromatic homogeneity and luminous efficiency are two crucial elements for determining a high-quality phosphor-converted LEDs (pc-LEDs). Thus, this paper provides essential information in choosing the particles to enhance lighting properties of high performance pc-LEDs. Scattering enhancement particles (SEP) such as CaCO3, CaF2, SiO2, and TiO2, are combined with yellow phosphor Y3Al5O12:Ce3+ and applied to the lighting devices. Initially, optical simulations are carried out with the support of LightTools program. Next, the Mie-theory is applied to calculate and confirm the results. The calculation subjects are SEPs scattering properties within the band 455 -595 nm. The scattering results of TiO2 suggest it is the optimal choice for pc-LEDs color quality in comparison to the other SEPs; however, it causes the luminous flux to decrease significantly along with the increase in its concentration. Besides, with the addition of SiO2 grains, we can accomplish higher lumen output at all particle sizes. Meanwhile, the application of 30% CaCO3 can decrease the CCT deviation by 620 K making CaCO3 the potential particle to be selected for chromatic quality and light output enhancement of pc-LEDs.